THE ATTITUDE OF MOTHERS IN REVITALIZING PUNJABI LANGUAGE: A CASE STUDY OF THE PUNJABI COMMUNITY IN MANJUNG DISTRICT, PERAK - Deepa a/p Visvanathan (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Punjabi is a small minority community in Malaysia among the approximately two million Indians in Malaysia. Punjabi people remain distinct from other people of Indian origins because of their religious beliefs and a strong sense of community. In the context of Malaysia, studies about the Punjabi community have not been encouraging and very minimal. As the Punjabi in Malaysia becomes more educated, the Punjabi community, which has long been undergoing a gradual shift into modern Malaysian society, and less emphasis is being placed on the ability to read and write Punjabi. The aim of this study is to obtain an overview of the language use patterns and language attitudes of Malaysian Punjabi mothers with the presence of their children. Specifically, the objective is to shed light on the importance of promoting Punjabi in the home domain by investigating whether the education and attitude of the mothers bring on the value of speaking the Punjabi language to their children in the home domain. A total of 11 respondents aged between 25 and 44 with children at or within the age of 6 were interviewed. One of the most significant findings of this study is the mismatch between language attitudes and actual language use by mothers with their children. The awareness exists in the mothers that Punjabi is important to their children to communicate with old age people and the Punjabi language is being used to do their prayers and to read their holy book. However, this positive attitude towards the language is not reflected in their language use and choice regardless of their education level. English dominated in most instances and most of the mothers claimed to be more comfortable speaking to their children in English.